Resistance to Organizational Change: A Case of Yemen National Oil and Gas Sector - A. M. Aamer; S. A. Sabra (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2019)
The purpose of this study was to evaluate barriers in understanding different sets of culture, which can arise in an organization. This study was also done to comprehend how resistance can be managed or reduced by discussing the significance of effective communication between management and employees. Trust in management and employee participation during the process of managing changes in National Oil and Gas Company was also identified. We conducted a case study as an investigative tool. In terms of the research site, we focused on one of the national oil and gas companies to highlight some of the issues and outcomes of recent management change. To collect data, questionnaires were distributed within the company. Bivariate correlation analysis and regression analysis were then used to test the proposed hypotheses. The results empirically showed that there are several parameters involving resistance to organizational changes. These parameters can be classified as communication between management and employees, trust in management, and employee participation. These parameters gave a positive impact as employee participation has the highest impact of the three examined factors.